Correlation of Body Mass Index with Handgrip Strength and Endurance of Dominant Hand in Medical Students - Shrestha, Lava; Gurung, Sanyukta; Bhat, Neeti; Mahotra, Narayan B; Bajimaya, Mahesh M; Kandel, Sabita; Malla, Neha; Shakya, Aman; Aryal, Vibina; Gyawali, Bigyan R; et al. (Journal of Institute of Medicine Nepal, 2020)
Introduction Hand grip strength is used in evaluation of muscle strength and is also increasingly being used as an indicator for nutritional status. The maximum force applied voluntarily by the subject is called maximum handgrip strength, which is measured in kilograms. Muscular endurance is the ability of a muscle or muscle group to perform against a load for an extended period of time, measured in seconds. This study aims to correlate body mass index with handgrip strength and handgrip endurance in medical students. Methods This is a cross sectional, observational study which included 74 undergraduate students of Maharajgunj Medical Campus by convenient sampling method. Body mass index was calculated by Quetelet’s formula. Camry digital hand dynamometer was used to measure handgrip strength in the dominant hand in kilograms. Participants were instructed to hold dynamometer with maintained pressure of 30% of maximum handgrip strength for as long as possible to determine the handgrip endurance. Statistical analyses were performed with SPSS Statistics software. Results The handgrip strength was more in males than females with a mean of 43.09±3.72 kg, while handgrip endurance was more in females with a mean of 123.60±50.65 sec. Positive correlation was seen between body mass index and handgrip strength (r=0.23 and p=0.045). Body mass index and handgrip endurance also showed positive correlation (r=0.34 and p=0.003). Conclusion Significant correlation of body mass index with handgrip strength and handgrip endurance was seen in medical students.